Новые виды клещей-фитосейид (Parasitiformes, Phytoseiidae) с переописанием Kuzinellus bregetovae - Колодочка, Л.А. (Вестник зоологии, 1993)
A description of new species from plants in the mountain region of Kirghizstan and a redescription of K. bregetovae are presented. Typhlodromus accessorius sp. n. is similar to T. pritchardi Arutunjan but differs in having solenostomes isc on dorsal schield, two denticles on Dm, different form of spermatheca. K. additionalis sp. n. is similar to K. bregetovae Wainstein et Beglarov but differs in having peritremae with pseudosetae contrary to smooth peritremae with longitudinal middle «crest» ot K. bregetovae, thickened blunt dorsal setae, form and size of spermathe-ca of female, form of spermatodactyl structure of male.